Measuring female factor in determinants of entrepreneurship: Illustration by case of Côte d'Ivoire through a quasi-experimental ex-post approach - Salif Koné (The Journal of Entrepreneurial Finance (JEF), 2022)
Purpose of this article is to find out whether determinants of women entrepreneurship are different from those of men's entrepreneurship in general and specifically in Côte d'Ivoire. To do this, we conducted a quasi-experimental analysis using non-parametric and parametric approaches to survey data on a sample of 161 entrepreneurs in Côte d'Ivoire, 113 of whom were women and 48 men. Our survey was designed and conducted to neutralize the socio-demographic and conjunctural differences between men and women entrepreneurship in order to produce matched data. Our analysis shows that determinants of male and female entrepreneurship in Côte d'Ivoire are not fundamentally different if rationality matters.
Keywords: L26; K28; C81; C14; 650; Entrepreneurship; female factor; quasi-experimental approach; non-parametric approach; parametric approach